Scald - Duhamel, Denise (Pitt poetry series., 2017)
When her "smart" phone keeps asking her to autocorrect her name to Denise Richards, Denise Duhamel begins a journey that takes on celebrity, sex, reproduction, and religion with her characteristic wit and insight. The poems in Scald engage feminism in two ways--committing to and battling with--various principles and beliefs. Duhamel wrestles with foremothers and visionaries Shulamith Firestone, Andrea Dworkin, and Mary Daly as well as with pop culture figures such as Helen Reddy, Cyndi Lauper, and Bikini Kill. In dialogue with artists and writers such as Catherine Opie, Susan Faludi, and Eve Ensler, Duhamel tries to understand our cultural moment. While Duhamel's Scald can burn, she has more importantly taken on the role of the ancient Scandinavian "Skald," one who pays tribute to heroic deeds. In Duhamel's case, her heroes are also heroines.